A misoginia, no período da ditadura, manifesta nos relatórios das Comissões Nacional da Verdade e dos Estados do Rio de Janeiro e de São Paulo, no contexto da justiça de transição a partir dos relatos de ex-presas políticas. - Coelho, Renata Santa Cruz (2024)
This research investigates whether the reports of the National Truth Commissions and the States of Rio de Janeiro and São Paulo, in the context of Transitional Justice, based on reports and questionnaires applied to former political prisoners, present the misogyny suffered by women during the dictatorship period. In view of this, I defined as a general objective: to evaluate whether the reports of the National Truth Commissions and the States of Rio de Janeiro and São Paulo, in the context of Transitional Justice, based on reports and questionnaires with former political prisoners, present the misogyny suffered by women during the dictatorship. Methodologically, the research is configured as follows: in terms of approach, qualitative, non-experimental in nature, with a basic purpose and, in terms of objectives, exploratory. In relation to procedures, bibliography and documents. To collect data, I made clippings from reports from the National Truth Commissions and the States of São Paulo and Rio de Janeiro. Furthermore, I administered a questionnaire to seven former political prisoners. The analysis movement took place based on Discourse Analysis and the theorists who supported this research. The results showed that both the Commissions' reports and the questionnaire applied to former political prisoners revealed practices of misogyny during the dictatorship period. Therefore, I conclude that misogyny was present in a systematic way, in the prison environment, and violence was organized by the gender hierarchy, reflected stereotypes, especially linked to sexuality, showing that torture was an instrument of state power and male domination and that the State used violence to nullify the victim’s personality.